2007
DOI: 10.1016/j.ymben.2006.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Application of microarrays to identify and characterize genes involved in attachment dependence in HeLa cells

Abstract: The ability to modify cellular properties such as adhesion is of interest in the design and performance of biotechnology-related processes. The current study was undertaken in order to evaluate the effectiveness of modulating cellular adhesion in HeLa cells from a genomics perspective. Using DNA microarrays, differences in gene expression between two phenotypically distinct, anchoragedependent and anchorage-independent, HeLa cell lines were identified. With the aid of several statistical methods and an extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 49 publications
2
28
0
1
Order By: Relevance
“…In a previous study, we identified two genes that have a role in cell adhesion (20): siat7e, a type II membrane glycosylating sialyltransferase, and lama4 which encodes laminin ␣4, a member of the laminin family of glycoproteins. These two genes were identified following a comparison of gene transcription of two phenotypically distinct HeLa cells, anchorage-dependent and anchorageindependent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, we identified two genes that have a role in cell adhesion (20): siat7e, a type II membrane glycosylating sialyltransferase, and lama4 which encodes laminin ␣4, a member of the laminin family of glycoproteins. These two genes were identified following a comparison of gene transcription of two phenotypically distinct HeLa cells, anchorage-dependent and anchorageindependent.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study we compared the transcription profiles of anchorage-dependent and anchorage-independent HeLa cells using DNA microarrays (20). The gene siat7e (ST6GalNac V) was identified as one of the genes that play a role in controlling the degree of cell adhesion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 1000 protein spots were detected on each gel. Spots, which were identified as being differentially expressed throughout culture and bright enough to allow for further processing (66), were analyzed using LC-MS/MS. Forty-six proteins were identified based on known CHO sequences and homology to other mammalian species (e.g., mouse, human) [18].…”
Section: Improving Metabolismmentioning
confidence: 99%
“…Its involvement in the inflammatory breast cancer phenotype (15) and in breast cancer metastases to the brain (16) has been reported. Alterations in the adhesive properties of HeLa cells by modulation of ST6GalNAcV expression has also been demonstrated (17). Interestingly, there is little to no α2,6-sialytransferase (ST6Gal1) activity, the enzyme that sialylates glycoprotein-associated, N-linked oligosaccharides, in malignant glioblastomas.…”
mentioning
confidence: 92%